A experiência educacional da administração popular em Porto Alegre/RS (1989-2004) na perspectiva de seus secretários municipais de educação - Gonçalves, Ana Cristina Rocha (2013)
The present doctoral thesis is a study case about the experience of management processes and educational policies developed by the Popular Administration in Porto Alegre/ RS, during its four governments from the perspective of the Municipal Secretaries of Education. This is a qualitative research that seeks to evaluate a new model of management of State and Education, which inserts through the policies of participative democracy the protagonism of citizens in the decision process and social control of public management. The theoretical and methodological framework developed in four initial chapters brings the concepts of citizenship, democracy, State, participative democracy and participation, from several theoretical and policies conceptions approach of the meanings and themes in the articulation between education, democracy and citizenship. Data collection was performed at two different times: in the first, a bibliographical research on the topic of this study, combined with a documentary research from publications of the Education City Department of Porto Alegre, official documents and legislation; In the second moment the field work, for which was made use of oral history, interviewing the Education Municipal Secretaries of Porto Alegre, in the period that the Popular Administration ruled that city (1989-2004), of the following administrations: second administration (1993 -1996), teacher Sônia Bruggemann Pilla; third administration (1997-2000), teacher José Clovis de Azevedo; and from fourth administration ( 2001- 2004 ), three secretaries: Teacher Eliezer Moreira Pacheco ( 2001- 2003 ); teacher Sofia Cavedon Nunes ( 2003-2004 ) and teacher Maria de Fátima Baierle (2004 ). Each chapter presents an evaluation of management addressing their continuities, advances, setbacks and breaks in optical research subjects. In the final chapter and considerations was made a balance of Popular Administration Governments in Porto Alegre seeking to ascertain in what extent this new model of State management and Education contributed to the process of democratization of the State, the Municipal System of Education and schools.